Moço em estado de sítio: rupture and experimentation in times of dictatorship - Borges, Luiz Paixão Lima (FCL-UNESP Laboratório Editorial, 2018)
This article intends to present some aesthetic and dramaturgicalaspects of the play Moço em estado de sítio, by Oduvaldo Vianna Filho. The playrepresents a qualitative leap in the dramaturgical production of an author whohas always looked at the contradictions of our society, trying to understand them,and responding to them through a conscious and committed work in the struggle for social transformation. By confronting his characters with objective reality, he demonstrates that his attachment to material forces dialectically conditions his human development. The dramaturgic form reveals such conditions in a metonymic relation, in order to unravel the social contradictions and, through this, to display the nature of the character in its process of formation and political action. The play inaugurates a cycle (Moço em estado de sítio, Mão na luva, Papa Highirte and Rasga coração) that uses flashbacks as a composition technique in order to deepen the psychological and dialectical realism.